How do regional price levels affect income inequality? Household-level evidence from 21 countries - Petr Janský; Marek Šedivý (Luxembourg Income Study (LIS), 2018)
Regional differences in prices levels are substantial in many countries, but little is known about how important they are for income inequality and relative poverty. To bridge this gap, we provide new evidence on the basis of the best available data and a novel two-step approach. First, we collect the largest cross-country dataset of regional price level estimates from 12 countries and use it to predict regional price levels in other countries. We then combine all these regional prices levels with household-level data from the Luxembourg Income Study, which gives us results for a final sample of 21 countries. We find that for some countries Gini coefficients and headcount poverty ratios are statistically significantly different when adjusted for regional price levels. For example, we show that adjusting for regional price levels would lower the Gini coefficients by 2% for Italy, 3% for Columbia and by 4% for Georgia, while it would increase the headcount poverty ratio by 6% for France and by 7% for Ireland. We conclude that regional price levels affect income inequality to a varying extent and should be taken into account by policy makers and in future research.
Keywords: D63; O18; R11; R58; 330; income inequality; relative poverty; regional price levels; regional purchasing power parities; Luxembourg Income Study